Multifunctional gelatin/chitosan electrospunwound dressing dopped with Undaria pinnatifida phlorotannin-enriched extract for skin regeneration - Ferreira, Carolina A. M. (2021)
The similarities of electrospun fibers with the skin extracellular matrix (ECM) make them promising structures for advanced wound dressings. Moreover, infection and resistance in wounds are a major health concern that may be reduced with antibacterial wound dressings. In this work, a multifunctional wound dressing was developed based on gelatin/chitosan hybrid fibers dopped with phlorotannin-enrich extract from the seaweed Undaria pinnatifida. The intrinsic electrospun structure properties combined with the antimicrobial and anti-inflammatory properties of phlorotannin-enrich extract will enhance the wound healing process. Electrospun meshes were produced by incorporating 1 or 2 wt% of extract, and the structure without extract was used as a control. Physico-chemical, mechanical, and biological properties were evaluated for all conditions. Results demonstrated that all developed samples presented a homogenous fiber deposition with the average diameters closer to the native ECM fibrils, and high porosities (~90%) that will be crucial to control the wound moist environment. According to the tensile test assays, the incorporation of phlorotannin-enriched extract enhances the elastic performance of the samples. Additionally, the extract incorporation made the structure stable over time since its in vitro degradation rates decreased under enzymatic medium. Extract release profile demonstrated a longstanding delivery (up to 160 days), reaching a maximum value of ~98% over time. Moreover, the preliminary antimicrobial results confirm the mesh’s antimicrobial activity against Pseudomonas aeruginosa and Staphylococcus aureus. In terms of biological characterization, no condition presented cytotoxicity effects on hDNF cells, allowing their adhesion and proliferation over 14 days, except the condition of 2 wt% after 7 days. Overall, the electrospun structure comprising phlorotannins-enriched extract is a promising bioactive structure with potential to be used as a drug delivery system for skin regeneration by reducing the bacterial infection in the wound bed.